2008
DOI: 10.1124/mol.108.046458
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Murine Organic Anion-Transporting Polypeptide 1b2 (oatp1b2/Slco1b2) Significantly Alters Disposition of Prototypical Drug Substrates Pravastatin and Rifampin

Abstract: Organic anion-transporting polypeptides (OATP) 1B1 and 1B3 are widely acknowledged as important and rate-limiting to the hepatic uptake of many drugs in clinical use. Accordingly, to better understand the in vivo relevance of OATP1B transporters, targeted disruption of murine Slco1b2 gene was carried out. It is noteworthy that Slco1b2(Ϫ/Ϫ) mice were fertile, developed normally, and exhibited no overt phenotypic abnormalities. We confirmed the loss of Oatp1b2 expression in liver using real-time polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 24 publications
13
112
0
Order By: Relevance
“…While the cause of the conjugated bilirubin elevation has not been determined, the increase in unconjugated bilirubin supports a role of Oatps in hepatocellular uptake of bilirubin. Mild elevation of mainly conjugated bilirubin is also observed in mice with inactivated Slco1b2 (Zaher et al, 2008), which was recently confirmed (Csanaky et al, 2011). Taken together, these human and animal data strongly support a physiological involvement of hepatocellular OATPs in the hepatic uptake of unconjugated and conjugated bilirubin.…”
Section: Bilirubinsupporting
confidence: 64%
“…While the cause of the conjugated bilirubin elevation has not been determined, the increase in unconjugated bilirubin supports a role of Oatps in hepatocellular uptake of bilirubin. Mild elevation of mainly conjugated bilirubin is also observed in mice with inactivated Slco1b2 (Zaher et al, 2008), which was recently confirmed (Csanaky et al, 2011). Taken together, these human and animal data strongly support a physiological involvement of hepatocellular OATPs in the hepatic uptake of unconjugated and conjugated bilirubin.…”
Section: Bilirubinsupporting
confidence: 64%
“…Although Slco1b2 -/-mice have already shown the impact of hepatic Oatp1b2 on liver uptake of some toxins, statins, and antibiotics (2,9,10), in this study we demonstrated that Oatp1a/1b effects an even more profound impact on drug pharmacokinetics by mediating (for some drugs, virtually all) hepatic uptake of drugs. This might have sweeping consequences for drug pharmacokinetics in patients, since many SNPs have been identified in the SLCO1B1, SLCO1B3, and SLCO1A2 genes, some of which are responsible for markedly reduced transport capacities (reviewed in ref.…”
Section: Figurementioning
confidence: 70%
“…For example, single Slco1b2 -/-mice have been generated and used to study the role of Oatp1b2 in plasma and liver distribution of toxins (phalloidin, microcystin-LR), statins (cerivastatin, lovastatin acid, pravastatin, and simvastatin acid) and antibiotics (rifampicin and rifamycin SV) (2,9,10). Furthermore, our group recently generated and characterized OATP1B1 transgenic mice, in which OATP1B1-mediated hepatic uptake of methotrexate (MTX) was demonstrated in vivo (11).…”
Section: Introductionmentioning
confidence: 99%
“…The detailed information regarding the generation of Oatp1b2 KO mice was described recently (Zaher et al, 2008). Briefly, a targeting vector to disrupt the Oatp1b2 murine gene was constructed using 4.1 kilobase (kb) of 5Ј homology and 5.0 kb of 3Ј homology.…”
Section: Materials Cerivastatin Was Purchased From Sequoia Research mentioning
confidence: 99%